An asymmetric bounce scenario to the dark energy ERA in f(Q,T) gravity - Narzary, Metoka; Dewri, Mukunda (Edelweiss Applied Science and Technology, 2025)
We explore the bouncing scenario within the f(Q,T) gravity framework in a Bianchi Type-VI background, utilizing a perfect fluid as the matter content. We take into account the idea of the bouncing model, as bouncing cosmology circumvents the initial singularity, preventing the universe from collapsing into a singular point. To elucidate the bouncing and late-time cosmological scenarios, we initially sought the exact solution to the field equations by assuming that the shear scalar (σ) is proportional to the expansion scalar (θ).To demonstrate the bouncing cosmology, we consider a bouncing scale factor given by R(t) = [1 + a₀ (t / t₀)²]ᵝ * exp1 / (α - 1) * [(tₛ - t) / t₀]^(1 - α). We also consider specific forms of f(Q,T) gravity expressed as f(Q,T) = a * Qᵏ + b * T, where Q and T denote the non-metricity scalar and the trace of the energy-momentum tensor, respectively. In this investigation, the Hubble parameter begins with a negative value, transitions through H = 0, and then exhibits a positive behavior, aligning with the outlined bouncing cosmology. Near the bouncing point, it is observed that the equation of state parameter crosses the phantom divide line (ω = -1). Then, we discuss the energy conditions, noting that both the null and strong energy conditions are violated in the vicinity of the bouncing point. The outcomes of this study may enhance our understanding of bouncing cosmological scenarios within the context of f(Q,T) gravity.